Quick of Blood (QB) Based on Body Weight Toward Urea Reduction Ratio (URR) on Hemodialysis Patients in Semarang Public Hospital - Sudiharto Sudiharto; Mardiyono Mardiyono; Arwani Arwani (Poltekkes Kemenkes Semarang, 2014)
This research is proper dose of Qb results in adequate URR upon 65%. To evaluate the effect of Qb based on weight on (URR) and MAP in CKD patients with hemodialysisThe study was quasi- experimental pre-post test two group design. The populations were patients with CKD and the samples were 30 subjects, 15 each group. The samples were recruited by consecutive sampling. URR were measured by ureum on pre-post hemodialysis. The setting of Qb by 4 x weight and (4 x BB) -10%. The data were analyzed using the setting of Qb by (4 x weight)-10% was better on URR and MAP than the setting of Qb by 4xweight in CKD patients with hemodialysis.